Transcranial Shear Wave Elastography of Neonatal and Infant Brains for Quantitative Evaluation of Increased Intracranial Pressure. Issue 11 (November 2019) - Dirrichs, Timm; Meiser, Nadia; Panek, Anna; Trepels-Kottek, Sonja; Orlikowsky, Thorsten; Kuhl, Christiane K.; Schrading, Simone
Abstract : Objectives: Increased intracranial pressure (ICP) in neonates and infants is a severe disease state that requires adequate diagnosis and, depending on the clinical situation and whether it is increasing, a rapid and efficient therapy. Clinical evaluation, B-mode ultrasound, and Doppler ultrasound give rise to a basic noninvasive diagnosis of increased ICP. The purpose of this prospective study was 2-fold: first, to analyze the technical feasibility of obtaining shear wave elastography (SWE) measurements of an infant's brain, and second, to compare the values of healthy neonates to those who have hydrocephalus and are either suspected of having or invasively shown to have increased ICP. Materials and Methods: This was a prospective, institutional review board–approved study of 184 neonates and infants with a mean age of 12 weeks (ranging from 1 day to 12 months). The final, technical evaluable cohort consisted of 166 infants, of whom 110 were healthy asymptomatic infants and 56 were diagnosed with hydrocephalus. Of the latter, 38 showed clinically increased ICP and 18 did not. Invasive ICP measurements were available from 47 of the children. All infants underwent systematic examination using B-mode ultrasound, Doppler ultrasound, and SWE using a high-resolution linear 15-MHz probe (Aixplorer; Supersonic), by 1 of 2 radiologists, each of whom had at least 5 years' experience examining children's brains and applying SWE. Semiquantitative and quantitative SWE measurements were performed. We compared the SWE values to each participant's clinical symptoms and to their invasive ICP measurement results. Correlations were calculated using Pearson and Spearman correlation coefficients. We used Student t test to compare the mean SWE values in healthy children to those of children with increased ICP. Results: Shear wave elastography in the brain was technically feasible, giving reliable SWE measurements in 110 (88.7%) of 124 of healthy children and in 56 (93.3%) of 60 children with hydrocephalus. Shear wave elastography values and, thus, rigidity in the brain's parenchyma were significantly higher in children with hydrocephalus (n = 56) than in healthy children (n = 110; mean, 21.8 kPa vs 14.1 kPa; P = 0.0083). A thorough correlation between invasive ICP measurements and SWE values in a subgroup of patients with hydrocephalus revealed a direct correlation between increased ICP and increased SWE values ( r = 0.69, P < 0.001). Mean SWE values were 30.8 kPa (range, 23.9–62.3 kPa) in patients with confirmed increased ICP (n = 35) versus 16.2 kPa (range, 10.2–41.9 kPa) in patients with nonincreased ICP (n = 12). Conclusions: Shear wave elastography is feasible in neonates with increased ICP and could be a useful additional diagnostic imaging and monitoring method for children verified or suspected to have increased ICP. However, more evidence is necessary to further evaluate the usefulness of SWE measurements in neonates with hydrocephalus. Clinical Relevance: Shear wave elastography can be used as a surrogate marker for ICP in neonates and infants.